Seed morphology and anatomy of Hypericum elegans Steph. ex Willd. - Szkudlarz, Piotr (Biodiversity: Research and Conservation, 2015)
Hypericum elegans is a rare perennial distributed primarily in Central and Eastern Europe. Seed morphology and anatomy in H. elegans was studied on the basis of a seed sample from its only locality in Poland. Scanning electron microscopy revealed that the seed coat of mature seeds is composed basically of 3 cell layers: epidermal, subepidermal and sclerenchymatic. They are documented graphically here.